A Rare case of Intranasal Craniopharyngloma - Dongol, Kripa; Gyawali, Bigyan Raj (Nepalese Journal of ENT Head and Neck Surgery, 2018)
Craniopharyngioma is a benign, slow growing  tumour with infrasellar location being very rare. Two histologic variants have been described in literature – papillary and adamantinomatous type. We present here a rare case of infrasellar adamantinomatous type of intranasal craniopharyngioma.Nepalese Journal of ENT Head and Neck Surgery, Vol. 5, No. 2, 2014, Page: 21-22